2021
DOI: 10.1038/s41467-021-25033-4
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 SUMOylates and stabilizes NLRP3 to facilitate inflammasome activation

Abstract: The cellular NLRP3 protein level is crucial for assembly and activation of the NLRP3 inflammasome. Various posttranslational modifications (PTMs), including phosphorylation and ubiquitination, control NLRP3 protein degradation and inflammasome activation; however, the function of small ubiquitin-like modifier (SUMO) modification (called SUMOylation) in controlling NLRP3 stability and subsequent inflammasome activation is unclear. Here, we show that the E3 SUMO ligase tripartite motif-containing protein 28 (TRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Interestingly, SENP3 action has a negative effect on speck formation and inflammasome activation in contrast to what SENP6 and SENP7 function ( Shao et al, 2020 ). Aligned with UBC9 data, Qin et al (2021) have described that E3 SUMO ligase tripartite motif-containing protein 28 (TRIM28) is an enhancer of NLRP3 inflammasome activation by facilitating NLRP3 expression. TRIM28 binds NLRP3, promotes SUMO1, SUMO2, and SUMO3 modification of NLRP3, and impairs NLRP3 ubiquitination degradation via proteasome.…”
Section: Inflammasome Components Sumoylationmentioning
confidence: 98%
“…Interestingly, SENP3 action has a negative effect on speck formation and inflammasome activation in contrast to what SENP6 and SENP7 function ( Shao et al, 2020 ). Aligned with UBC9 data, Qin et al (2021) have described that E3 SUMO ligase tripartite motif-containing protein 28 (TRIM28) is an enhancer of NLRP3 inflammasome activation by facilitating NLRP3 expression. TRIM28 binds NLRP3, promotes SUMO1, SUMO2, and SUMO3 modification of NLRP3, and impairs NLRP3 ubiquitination degradation via proteasome.…”
Section: Inflammasome Components Sumoylationmentioning
confidence: 98%
“…In addition to regulating a diverse set of viruses, KAP1 has been implicated in a variety of host biological processes including innate immunity, tumor microenvironment regulation, and immune cell development, among others ( Czerwinska et al., 2020 ; Lee et al., 2020 ; Liang et al., 2020 ; Liu et al., 2020 ; Chikuma et al, 2021 ; Park et al., 2021 ) ( Figure 3 ). While some of these reported KAP1-dependent functions are mediated by KAP1 repression of ERVs ( Tie et al., 2018 ; Schmidt et al., 2019 ; Lee et al., 2020 ), many of these cellular roles have been mediated by KAP1 regulating transcription of host genes ( Kamitani et al., 2008 ; Wang et al., 2017 ) or through KAP1 utilizing its E3 ubiquitin ligase function to degrade specific factors ( Liang et al., 2011 ; Qin et al., 2021 ).…”
Section: Kap1 Regulation Of Cell Fate Responses and Immune Cell Funct...mentioning
confidence: 99%
“…Interestingly, inflammasome activation tends to upregulate NO generation suggesting an autoregulatory mechanism (Yang et al, 2017). Recent studies have demonstrated that SUMOylation of NLRP3 by UBC9-directed SUMO1 and TRIM28-directed SUMO1-3 are important for inflammasome activation and that de-SUMOylation by the SUMO-specific protease SENP3 can reduce inflammasome activation (Shao et al, 2020;Qin et al, 2021). ADP-ribosylation of NLRP3 by the Mycoplasma pneumoniae CARDS-toxin can trigger inflammasome activation for a robust inflammatory response (Bose et al, 2014).…”
Section: Other Post-translational Modificationsmentioning
confidence: 99%